Few-layer fluorine-functionalized graphene hole-selective contacts for efficient inverted perovskite solar cells - Hanmandlu, Chintam; Sahoo, Mamina; Liu, Chi-Ching; Chen, Hsin-An; Pao, Chun-Wei; Chang, Yun-Chorng; Chu, Chih-Wei; Lai, Chao-Sung (Chemical engineering journal (Lausanne, Switzerland : 1996), 2022)
We have studied the use of fluorographene (FGr) as the hole transport material (HTL) to replace the most commonly used PEDOT: PSS in inverted perovskite solar cells (PSCs). The presence of the FGr improved the power conversion efficiency to 19.34%, the highest ever reported for a PSC incorporating a graphene functionalized transport material. Furthermore, the FGr HTL exhibits promising potential for application in flexible PSCs. [Display omitted] •The FGr, bonds strongly with the conductive oxide and the perovskite surface, while being impervious to chemical degradation.•An energetically aligned interface with the perovskite absorbing layer, without undergoing non-radiative losses.•A stabilized PCE of up to 19.34% with an exceptional fill factor of 83.84 %.•A flexible PSCs achieving PCE of 17.5% with good bending stability. Charge-selective contacts can play a critical role in enhancing the efficiency of perovskite solar cells (PSCs). In this study, we employed fluorine-functionalized graphene (FGr) layers having finely tunable energy levels as hole transport layers (HTLs) to improve the power conversion efficiency (PCE) and stability of inverted PSCs. The non-wetting surface of the FGr enhanced the crystallinity of organic–inorganic perovskites films with large aspect ratios, relative to that of poly(3,4-ethylenedioxythiophene):polystyrenesulfonate (PEDOT:PSS). Combining the high work function of the HTL interface with the enhanced crystallinity and limited grain boundary area dramatically decreased the charge recombination losses in organic–inorganic trihalide perovskite (OTP) films. Thus, when incorporating FGr HTLs in inverted PSCs, the best PCE reached 19.34%—the highest efficiency reported to date for any PSC featuring a functionalized graphene HTL. Furthermore, we used this HTL to prepare flexible PSCs and obtained a highest efficiency of 17.50%. Therefore, this highly applicable and facile interface strategy using functionalized graphene HTLs provides stable PSCs displaying high PCEs.